Some Aspects of Tuberculous Lung Lesions in Covid Patients (Texas Journal of Medical Science, 2023)
A comprehensive analysis of 215 patients with tuberculosis and new coronavirus infection (COVID-19) showed that 40 (18.6%) were referred by anti-tuberculosis institutions, 174 (80.9%) by the general medical network, and one (0.5%) applied for help yourself. Tuberculosis was detected earlier than the COVID-19 attack in 41 (19.1%) cases, specific changes in the lungs were detected simultaneously or later than viral pneumonia in 174 (80.9%).